EFEKTIVITAS TUGAS KEPALA DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA GEMILANG JAYA KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Okberi, Erik; Khotami, Khotami; Herman, Herman (UIR PRESS, 2022)
This research aims to determine the extent of the Effectiveness of the Duties of the Village Head in Infrastructure Development in Gemilang Jaya Village, Indragiri Hilir district, The indicators in this research are: Clarity of Program Objectives, Program Policies, Facilities and Infrastructure. The type of research located in the Office of the Head of Gemilang Jaya Village, Batang Tuaka District, Indragiri Hilir Regency is a qualitative descriptive research type, because it explores and analyzes the effectiveness of the village head's duties in infrastructure development in Gemilang Jaya Village. Qualitative Research Method is a method used to examine natural objects. Results of Methods Qualitative research emphasizes meaning rather than generalizations. Data collection techniques and types used in this study include: observation, interviews, documentation, and books. Based on the analysis technique, the researcher considers that development planning starting from the clarity of program objectives, program policies, and facilities and infrastructure is still not active.